The Writing on the Wall : Chinese and Japanese Immigration to BC, 1920 - Glynn-Ward, Hilda, 1887-1966 (Book collections on Project MUSE., 2010)
The Writing on the Wall is a vivid illustration of the fear and prejudice with which immigrants were regarded in the early twentieth century.